Kualitas Lingkungan Permukiman Masyarakat Suku Bajo di Daerah yang Berkarakter Pinggiran Kota dan Daerah Berkarakter Pedesaan di Kabupaten Muna - Ridwan, Ucok Heriady; Giyarsih, Sri Rum (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The study aims to analyze the settlement environmental quality of the Bajo tribe in Lagasa village (representing suburban environment) and in Latawe village (representing rural environment) of Muna regency. The survey included structured interview with 30 hourseholds of Bajo tribe in each of the two villages. The assessment of settlement environmental quality included three indicators comprising house condition, sanitation and basic infrastructure. The study found disparity of settlement environmental quality among the two villages. Lagasa village which represent suburban environment has better quality compared to Latawe village which represent rural environment. The degree of accessibility was found to have a crucial role in causing the disparity.